Digitalisasi Informasi Kelembagaan Sekolah Darul Hikam sebagai Implementasi Sistem Informasi Manajemen - Teguh Iqbal Maulana Al-Hamidi (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the digitalization of Darul Hikam School's institutional information as a form of implementation of a Management Information System (MIS) in the context of educational management. This study uses a qualitative approach with a descriptive-analytical method. Data were obtained through analysis of documents and digital content available on the official website of Darul Hikam School, including the school profile, vision and mission, educational programs, and menu structure and information services. The data analysis technique was carried out using content analysis which classifies information into strategic, operational, and service categories in accordance with the MIS theoretical framework. The results show that the digitalization of Darul Hikam School's institutional information has fulfilled the basic functions of MIS in the aspects of information management and presentation. Strategic information is reflected through the digitalization of the school profile and vision and mission which serve as the basis for planning and institutional identity. Operational information is shown through the presentation of diverse and structured educational programs, while service information is realized through the registration menu, activity news, and communication tools with the community. The organized website structure indicates that the school website plays a role as a MIS subsystem in supporting transparency, accountability, and educational services. This study concludes that the digitalization of Darul Hikam School's institutional information is the initial stage of MIS implementation in educational management. Although not yet fully integrated with a data-driven decision-making system, the digitalization practices undertaken have strategic value as a foundation for the development of a more comprehensive MIS in the future. This research contributes to enriching the study of educational MIS by highlighting the role of school websites as part of a management information system, particularly in the context of Islamic schools in Indonesia. Keywords: Digitalization of information, management information systems, school websites, education management, Islamic schools   Abstrak Penelitian ini bertujuan untuk menganalisis digitalisasi informasi kelembagaan Sekolah DarulHikam sebagai bentuk implementasi Sistem Informasi Manajemen (SIM) dalam konteks manajemen pendidikan. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif-analitis. Data diperoleh melalui analisis dokumen dan konten digital yang tersedia pada website resmi Sekolah Darul Hikam, meliputi profil sekolah, visi dan misi, program pendidikan, serta struktur menu dan layanan informasi. Teknik analisis data dilakukan dengan analisis konten (content analysis) yang mengklasifikasikan informasi ke dalam kategori informasi strategis, operasional, dan layanan sesuai dengan kerangka teori SIM. Hasil penelitian menunjukkan bahwa digitalisasi informasi kelembagaan Sekolah Darul Hikam telah memenuhi fungsi dasar SIM pada aspek pengelolaan dan penyajian informasi. Informasi strategis tercermin melalui digitalisasi profil sekolah serta visi dan misi yang berfungsi sebagai landasan perencanaan dan identitas kelembagaan. Informasi operasional ditunjukkan melalui penyajian program pendidikan yang beragam dan terstruktur, sedangkan informasi layanan diwujudkan melalui menu pendaftaran, berita kegiatan, dan sarana komunikasi dengan masyarakat. Struktur website yang terorganisasi menunjukkan bahwa website sekolah berperan sebagai subsistem SIM dalam mendukung transparansi, akuntabilitas, dan layanan pendidikan. Penelitian ini menyimpulkan bahwa digitalisasi informasi kelembagaan Sekolah Darul Hikam merupakan tahap awal implementasi SIM dalam manajemen pendidikan. Meskipun belum sepenuhnya terintegrasi dengan sistem pengambilan keputusan berbasis data, praktik digitalisasi yang dilakukan memiliki nilai strategis sebagai fondasi pengembangan SIM yang lebih komprehensif di masa depan. Penelitian ini berkontribusi dalam memperkaya kajian SIM pendidikan dengan menegaskan peran website sekolah sebagai bagian dari sistem informasi manajemen, khususnya dalam konteks sekolah Islam di Indonesia. Kata kunci: Digitalisasi informasi, sistem informasi manajemen, website sekolah, manajemen pendidikan, sekolah Islam